Understanding Depletion Induced Like-Charge Attraction from Self-Consistent Field Model (Communications in Computational Physics, 2019)
The interaction force between likely charged particles/surfaces is usuallyrepulsive due to the Coulomb interaction. However, the counterintuitive like-chargeattraction in electrolytes has been frequently observed in experiments, which has beentheoretically debated for a long time. It is widely known that the mean field Poisson-Boltzmann theory cannot explain and predict this anomalous feature since it ignoresmany-body properties. In this paper, we develop efficient algorithm and perform theforce calculation between two interfaces using a set of self-consistent equations whichproperly takes into account the electrostatic correlation and the dielectric-boundary effects. By solving the equations and calculating the pressure with the Debye-chargingprocess, we show that the self-consistent equations could be used to study the attraction between like-charge surfaces from weak-coupling to mediate-coupling regimes,and that the attraction is due to the electrostatics-driven entropic force which is significantly enhanced by the dielectric depletion of mobile ions. A systematic investigationshows that the interaction forces can be tuned by material permittivity, ionic size andvalence, and salt concentration, and that the like-charge attraction exists only for specific regime of these parameters.
Keywords: Like-charge attraction; self-consistent field model; dielectric-boundary effect; correlation energy; Green's function.